Analisis Faktor yang Mempengaruhi Kepatuhan Menjalankan Diet pada Lansia Penderita Diabetes Mellitus Tipe Dua - Zeilen Fitriana; Eka Asvista Salviana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the factors that affect dietary compliance in patients with type II diabetes mellitus, including family support, knowledge, income, and nutritional counseling. The research method used in this study is cross-sectional. This study indicates a relationship between family support, understanding, revenue, and nutritional counseling on dietary compliance in older people with type II diabetes Mellitus in 2019 in a district in Jambi. In conclusion, there is a relationship between family support, knowledge, income, and nutritional counseling on dietary compliance in older people with type II diabetes Mellitus. Keywords: Diabetes Mellitus, Family Support, Knowledge, Nutrition Counseling